2013
DOI: 10.1038/ncb2873
|View full text |Cite
|
Sign up to set email alerts
|

Somatic cells regulate maternal mRNA translation and developmental competence of mouse oocytes

Abstract: Germ cells divide and differentiate in a unique local microenvironment under the control of somatic cells. Signals released in this niche instruct oocyte reentry into the meiotic cell cycle. Once initiated, the progression through meiosis and the associated program of maternal mRNA translation are thought to be cell-autonomous. Here we show that translation of a subset of maternal mRNAs critical for embryo development is under the control of somatic cell inputs. Translation of specific maternal transcripts inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
115
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 48 publications
6
115
0
1
Order By: Relevance
“…Upon meiotic maturation, oocytes undergo two consecutive M phases and arrest again at metaphase of meiosis II (MII). Many maternal mRNAs are translationally activated during this process (Chen et al, 2013;Piccioni et al, 2005). These temporally translated proteins play key roles in meiotic spindle assembly, MII arrest maintenance and mRNA clearance during maternalzygotic transition (MZT).…”
Section: Introductionmentioning
confidence: 99%
“…Upon meiotic maturation, oocytes undergo two consecutive M phases and arrest again at metaphase of meiosis II (MII). Many maternal mRNAs are translationally activated during this process (Chen et al, 2013;Piccioni et al, 2005). These temporally translated proteins play key roles in meiotic spindle assembly, MII arrest maintenance and mRNA clearance during maternalzygotic transition (MZT).…”
Section: Introductionmentioning
confidence: 99%
“…In general, this is achieved by modulating mRNA polyadenylation where translation is suppressed by poly-adenylation and activated by deadenylation to induce development and meiosis (11)(12)(13). Recent data have shown that translation of a subset of oocyte mRNAs that are critical for early embryo development are also under the control of surrounding follicular (granulosa) cell inputs (14), but the signals are still poorly understood.…”
mentioning
confidence: 99%
“…In follicle, activation of ERK1/2 is central for induction of oocyte maturation by the EGF pathway since inhibition of the EGF receptor abrogates cumulus expansion, oocyte maturation, and ovulation (46,47). Recently, it has been shown that cumulus cell derived EGF-like peptide (AREG) regulates translation of a subset of transcripts within the mouse oocyte during maturation, and perturbation of this factor affects oocyte quality (10). These reports indicate an important role of cAMP in oocyte maturation and acquisition of developmental competence through the EGF pathway.…”
mentioning
confidence: 99%